2018
DOI: 10.7717/peerj.4357
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the scholarly mega-journal, 2006–2017

Abstract: Mega-journals are a new kind of scholarly journal made possible by electronic publishing. They are open access (OA) and funded by charges, which authors pay for the publishing services. What distinguishes mega-journals from other OA journals is, in particular, a peer review focusing only on scientific trustworthiness. The journals can easily publish thousands of articles per year and there is no need to filter articles due to restricted slots in the publishing schedule. This study updates some earlier longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 12 publications
0
39
0
3
Order By: Relevance
“…Monthly is the most common frequency of SCI journals, while quarterly is the most common frequency of SSCI journals. The "mega journal" phenomenon described by Björk [3,4], Spezi et al [5], Wakeling et al [13], and others has not become a mainstream practice among SCI and SSCI journals, since only one sample (Sustainability, an SSCI monthly OA journal) of this study could be characterized as a "mega journal". "Issueless", described by Björk [3], has not become a common practice among SCI and SSCI journals either.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Monthly is the most common frequency of SCI journals, while quarterly is the most common frequency of SSCI journals. The "mega journal" phenomenon described by Björk [3,4], Spezi et al [5], Wakeling et al [13], and others has not become a mainstream practice among SCI and SSCI journals, since only one sample (Sustainability, an SSCI monthly OA journal) of this study could be characterized as a "mega journal". "Issueless", described by Björk [3], has not become a common practice among SCI and SSCI journals either.…”
Section: Resultsmentioning
confidence: 75%
“…Björk [3] also mentioned in the same study that issueless publishing has become mainstream in OA publishing. Based on his own 2015 study, Björk [4] in 2018 studied 19 journals he categorized as mega journals and found that the "Big Two" mega journals, Scientific Reports and PLOS One, published a total of 41,175 articles in 2017. Björk [4] also found that 25% authors of these 19 mega journals are affiliated with Chinese institutions, with IEEE Access having 55% authors from China in 2017.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…APCs were a response to the loss of revenue incurred by journals for no longer charging subscriptions. They enabled, for instance, a new form of journal known as the mega-journal pioneered by the Public Library of Science One (PLOS One) and were quickly co-opted by the major traditional publishers (Björk, 2018). In some fields, journals supported by APCs are well established (Berger & Cirasella, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%